Advantages & disadvantages of containerization - Ali, Noor Malinjasari; Mohd Noor, Hasmida; Mohamed Nor, Raslina; Mat Salleh, Suzila; Hamzah, Siti Fatimah Mardiah; A Rashid, Ruzaidah (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
Material handling economy is typically proportional to the size of the load handled. As the size of the load increases, the fewer the number of trips required to store a given quantity of goods, the better the economy. The number of trips is connected directly to the labor time required to move the goods as well as the time that the material handling equipment is in service. Efficiency can often be enhanced by consolidating a number of small packages into a single load and then handling the consolidated load.